SISTEM INFORMASI ADMINISTRASI DATA SISWA BERBASIS WEB PADA SMK SWASTA PEMBANGUNAN BAGAN BATU - Siharningish Siharningish; Volvo Sihombing; Masrizal Masrizal (Politeknik Bisnis Indonesia, 2021)
The very rapid development of technology has brought humans into life side by side with information and technology itself. For now, there are more and more private companies, educational institutions and institutions whose needs are used as information services. Processing of student data at the Private SMK Bagan Batu Development School which still uses the manual method makes data searching and printing reports slow and less efficient. To solve this problem, a web-based student data administration processing information system was designed at the Bagan Batu Development Private Vocational School. This web-based information system was built using the PHP and HTML programming languages, as well as the Cascading Style Sheet (CSS) as content representation, and database processing using MySQL. The result of this study is an information system that facilitates the work of administrative staff at the Chartered Construction Private Vocational School in administering student data so that student data administration activities can be carried out easily, quickly and efficiently.